2005
DOI: 10.1021/cm049063x
|View full text |Cite
|
Sign up to set email alerts
|

1H MAS, 15N CPMAS, and DFT Investigation of Hydrogen-Bonded Supramolecular Adducts between the Diamine 1,4-Diazabicyclo-[2.2.2]octane and Dicarboxylic Acids of Variable Chain Length

Abstract: Supramolecular adducts of formula [N(CH2CH2)3N]−H−[OOC(CH2) n COOH] (n = 1−7) have been obtained by mechanochemical reaction of solid dicarboxylic acids of variable chain length HOOC(CH2) n COOH (n = 1−7) with solid 1,4-diazabicyclo[2.2.2]octane (dabco). 1H MAS and 15N CPMAS spectra have been measured to investigate the presence of intermolecular hydrogen bonds between acid and base. Proton and nitrogen chemical shifts allow a distinction to be made between N+−H···O- interactions (with proton transfer) and N··… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 92 publications
(207 reference statements)
5
69
0
Order By: Relevance
“…Frey and Sternberg [49,50] have observed direct relationships between d In a previous paper we have investigated the proton transfer reaction along a hydrogen bond between aliphatic dicarboxylic acids and the diamine base 1,4-diazabicyclo-[2.2.2]octane (DABCO), by means of 1 H, 13 C, and 15 N solidstate NMR spectroscopy. [51] We founded that the isotropic 13 C chemical shift moved to higher frequencies as it passes from the carboxylic acid to the carboxylate form. The 13 C chemical shift tensor analysis of the carboxylic group showed that d 22 is the most sensitive parameter, changing from 192 AE 6 for the deprotonated form to 162 AE 5 ppm for the protonated form.…”
Section: Introductionmentioning
confidence: 88%
“…Frey and Sternberg [49,50] have observed direct relationships between d In a previous paper we have investigated the proton transfer reaction along a hydrogen bond between aliphatic dicarboxylic acids and the diamine base 1,4-diazabicyclo-[2.2.2]octane (DABCO), by means of 1 H, 13 C, and 15 N solidstate NMR spectroscopy. [51] We founded that the isotropic 13 C chemical shift moved to higher frequencies as it passes from the carboxylic acid to the carboxylate form. The 13 C chemical shift tensor analysis of the carboxylic group showed that d 22 is the most sensitive parameter, changing from 192 AE 6 for the deprotonated form to 162 AE 5 ppm for the protonated form.…”
Section: Introductionmentioning
confidence: 88%
“…Direct relationships between δ 1 H and HB strength and between δ 1 H and X-H distance for different classes of hydrogenbonded compounds have been reported. 37 Thus, NMR shift data can be used to detect and to estimate the presence and the strength of HBs (Scheme 1).…”
Section: The Hydrogen Bondmentioning
confidence: 99%
“…The 1 H spectrum of the adduct between malonic acid and DABCO, reported in Figure 4(a), clearly shows in the high frequency region two well defined HB signals at 17.6 and 12.4 ppm that can be assigned to the O-H· · ·O and the N + -H· · ·O − protons, respectively (Figure 4b). 37 Owing to the intrinsic difficulty of X-ray techniques in detecting the hydrogen atom position, an effective method that combines 1 H fast MAS NMR and density functional theory (DFT) calculation for the determination of the O-H distance has been proposed. 38 It consists in refining the hydrogen atom position within the HB, in which the computed 1 H δ are reported as a function of the O-H distance while all other atoms are retained at their positions.…”
Section: The Hydrogen Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [14][15][16][17][18] ), ab initio calculations of NMR properties in the solid state are less developed. A first attempt to compute the magnetic shielding in molecules was performed by using localized atom-centred basis sets, based on the Molecular Orbital Theory.…”
Section: Introductionmentioning
confidence: 99%